UNIQUE SITES OF PILGRIMAGE TOURISM IN BUKHARA - Makhfuza Fakhruddinovna Alimova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
At present, the tourism industry has become one of the key sectors contributing to the socio-cultural life of our country, its economic progress, and its reputation on a global scale. In today’s world, tourism is developing through a variety of forms such as ecotourism, sports tourism, excursion tourism, extreme tourism, gastronomic tourism, cultural tourism, and pilgrimage tourism. In this regard, the Republic of Uzbekistan is also undertaking a range of initiatives and large-scale reforms in the field of pilgrimage tourism.